THE IMPACT OF THE CONVERGENCE OF REGULATIONS AND INFORMATION TECHNOLOGY IN INCREASING LOGISTICS COMPETITIVENESS AT PT. FAB ENTERPRISES LOGISINDO - Barata, Fausta Ari (LPPM Universitas Jambi, 2026)
Determine the impact of the convergence of regulations and information technology in increasing logistics competitiveness at PT. Fab Enterprises Logisindo. Quantitative research by looking at the problems and research objectives to be achieved, this research uses a quantitative research approach with a survey approach. The object of this research is PT. Fab Enterprises Logisindo with 100 employees. Data analysis uses the Partial Least Square (PLS) approach using Smart PLS software. The research results show that there is a significant influence of regulatory convergence on logistics competitiveness at PT. Fab Enterprises Logisindo. There is a significant influence of information technology on logistics competitiveness at PT. Fab Enterprises Logisindo and information technology variables mediate the influence of regulatory convergence on logistics competitiveness at PT. Fab Enterprises Logisindo. Thus, the better the regulatory convergence, the more competitiveness supported by information technology can be increased. Meanwhile, logistics competitiveness needs to be increased by implementing competitive prices and service innovations, to create certain uniqueness and contribute to the creation of logistics competitive advantage. The novelty of this research lies in the integration model of regulatory convergence and information technology within a single structural framework to explain logistics competitiveness. Unlike previous studies that tend to examine regulation and technology separately, this study highlights the mediating role of information technology, showing that regulatory convergence alone is not sufficient to enhance competitiveness without technological support. This integrated approach provides a more comprehensive explanation of how logistics competitive advantage is formed in a practical corporate context.